Juventudes e as emoções: narrativas universitárias a partir da pandemia COVID-19 no Brasil - Paulo, Lúcia Verônica Muniz de (2024)
This research is an ethnographic work in which I sought to understand the meanings of the emotional experiences experienced by young people during and after the COVID-19 pandemic in Brazil. I was able to develop it in the Graduate Program in Anthropology at the Federal University of Sergipe – PPGA/UFS, and I had as interlocutors the young students of the various undergraduate courses of this same institution who experienced the remote teaching model during periods of social distancing. Based on Margaret Mead (2015 [1928]), who asked herself "what explains the presence of disorder and tension among American adolescent girls?" (p. 31), I raise the question: what explains the increase in mental disorders among young Brazilians? Although emotions are presented based on what is felt in the body of individuals, their meanings and interpretations have origins found in the collectively constructed social body (ABULUGHOD; LUTZ, 1990, p. 13). The objective here was to analyze how the pandemic in Brazil, as a context of confluence of crises – a health crisis added to the political-social crisis – influenced the production of young narratives about emotions and suffering. The experiences caused by the pandemic were not signified individually, but based on the sharing and exchanges provided by the social life established by the period of crises. I was able to apprehend part of the reflections of these exchanges through fieldwork and the use of the questionnaire of this investigation, which allowed me to observe the interactions and meanings narrated by the interlocutors. The attempt here, therefore, was to identify the ways in which young people, within this scenario of confluence of crises, produced and signified their emotional experiences (FEIXA, 2021b), without ignoring that this context was marked by instabilities in Brazilian institutions and the rise of an alt-right and neoliberal government.